2021
DOI: 10.3390/su13105603
|View full text |Cite
|
Sign up to set email alerts
|

The Restorativeness of Outdoor Historical Sites in Urban Areas: Physical and Perceptual Correlations

Abstract: Growing tourist flows, which crowd ancient city centres, have modified their liveability and threatened conservation. They have increased the need for quiet places, primarily where green parks are missing. While previous studies have highlighted the possibility of reusing hidden sites of historical buildings, it is not clear if this scheme can also be applied in other contexts, and which physical or perceptual dimensions are mainly related to the restoration of these sites. If greenery and water elements induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Due to the high potential of fascination, places with high historical and architectural value can also provide high restorative effects ( Weber and Trojan, 2018 ). This is also confirmed by the recent studies of Wang et al (2023) on typical cultural heritage sites in China and Masullo et al (2021b) on Italian cloisters and Turkish Khan. For Galindo and Hidalgo (2005) and Hidalgo et al (2006) , cultural-historical and recreational places were considered more attractive than panoramic places and housing areas.…”
Section: Introductionsupporting
confidence: 80%
“…Due to the high potential of fascination, places with high historical and architectural value can also provide high restorative effects ( Weber and Trojan, 2018 ). This is also confirmed by the recent studies of Wang et al (2023) on typical cultural heritage sites in China and Masullo et al (2021b) on Italian cloisters and Turkish Khan. For Galindo and Hidalgo (2005) and Hidalgo et al (2006) , cultural-historical and recreational places were considered more attractive than panoramic places and housing areas.…”
Section: Introductionsupporting
confidence: 80%
“…Fornara and Troffa (2009) confirmed that historic sites and urban parks have similar restorative qualities and characteristics. Masullo et al (2021b) indicated that historical–artistic features present in historical sites are closely related to all the components of restorativeness, particularly the component of fascination. Liu et al (2019) indicated that a positive soundscape perception in historic blocks could contribute to visitor satisfaction during the visiting experience.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…Additionally, as shown in Table 5, they are also important indicators of feelings of fascination. Masullo et al (2021) found that the dimension most influenced by the component aspects of history and culture is fascination [74]. Therefore, preserving and enhancing the value of cultural heritage is a key proposition in the future of green cultural heritage.…”
Section: Driving Factors For the Restorative Experience Of Green Cult...mentioning
confidence: 99%